Frequent Long-Range Epigenetic Silencing of Protocadherin Gene Clusters on Chromosome 5q31 in Wilms' Tumor - Dallosso, Anthony R. (Public Library of Science, 2009)
Wilms' tumour (WT) is a pediatric tumor of the kidney that arises via failure of the fetal developmental program. The absence of identifiable mutations in the majority of WTs suggests the frequent involvement of epigenetic aberrations in WT. We therefore conducted a genome-wide analysis of promoter hypermethylation in WTs and identified hypermethylation at chromosome 5q31 spanning 800 kilobases (kb) and more than 50 genes. The methylated genes all belong to α-, β-, and γ-protocadherin (PCDH) gene clusters (Human Genome Organization nomenclature PCDHA@, PCDHB@, and PCDHG@, respectively). This demonstrates that long-range epigenetic silencing (LRES) occurs in developmental tumors as well as in adult tumors. Bisulfite polymerase chain reaction analysis showed that PCDH hypermethylation is a frequent event found in all Wilms' tumor subtypes. Hypermethylation is concordant with reduced PCDH expression in tumors. WT precursor lesions showed no PCDH hypermethylation, suggesting that de novo PCDH hypermethylation occurs during malignant progression. Discrete boundaries of the PCDH domain are delimited by abrupt changes in histone modifications; unmethylated genes flanking the LRES are associated with permissive marks which are absent from methylated genes within the domain. Silenced genes are marked with non-permissive histone 3 lysine 9 dimethylation. Expression analysis of embryonic murine kidney and differentiating rat metanephric mesenchymal cells demonstrates that Pcdh expression is developmentally regulated and that Pcdhg@ genes are expressed in blastemal cells. Importantly, we show that PCDHs negatively regulate canonical Wnt signalling, as short-interfering RNA–induced reduction of PCDHG@ encoded proteins leads to elevated β-catenin protein, increased β-catenin/T-cell factor (TCF) reporter activity, and induction of Wnt target genes. Conversely, over-expression of PCDHs suppresses β-catenin/TCF-reporter activity and also inhibits colony formation and growth of cancer cells in soft agar. Thus PCDHs are candidate tumor suppressors that modulate regulatory pathways critical in development and disease, such as canonical Wnt signaling.